Deep brain stimulation combined with morroniside promotes neural plasticity and motor functional recovery after ischemic stroke - Chen, Yanxi; Xu, Zhidong; Ma, Yifu; Liu, Tingting; Tian, Xin; Zhu, Zixin; Zheng, Wenrong; Wang, Yufeng; Zheng, Ruifang; Xing, Jianguo; Wang, Wen; Sun, Fangling (Frontiers in Pharmacology, 2024)
Background and Objective: Until now, there has been an unmet need for treatments promoting chronic-phase post-stroke functional recovery. We previously found that morroniside promoted endogenous neurogenesis in ischemic stroke, but its therapeutic window was limited to the first 48 h. Here, we aimed to explore whether deep brain stimulation (DBS) combined with morroniside could enhance neurogenesis in rats subjected to focal ischemic stroke and contributes to functional recovery.Methods: Beginning two weeks after the endothelin-1-induced stroke, rats were administered DBS of lateral cerebellar nucleus consecutively for 14 days, followed by morroniside for 7 consecutive days post-stimulation. Behavioral tests were used for assessing motor function. Local field potentials were recorded to evaluate neuronal excitability. Nissl staining was used to assess infarct volume. Immunofluorescence staining and western blotting were carried out to uncover the stroke recovery mechanisms of DBS combined with morroniside treatment.The results showed that this combined treatment improved behavioral outcomes, enhanced cortical local field potentials, and diminished infarct volumes at 35 days post-stroke. Moreover, it notably amplified neurogenic responses post-stroke, evidenced by the proliferation of BrdU/SOX and BrdU/DCX in the subventricular zone, and their subsequent differentiation into BrdU/NeuN and BrdU/VgulT1 in the ischemic penumbra. Moreover, the combined treatment also elevated the amount of BrdU/Olig2 and the level of axonal sprouting-related proteins in the perilesional cortex.Our results demonstrated that the combined treatment extended the neurorestorative efficacy of morroniside, reduced infarct size, enhanced neuronal excitability and accelerated sensorimotor function recovery. This therapeutic approach may emerge as a potential clinical intervention for chronic ischemic stroke.